Social stratification and mobility - Sharma, K. L. (Kanhaiya Lal), 1941- (Jaipur : Rawat Publications, 1994)
With reference to India.
Includes bibliographical references and index.
Keywords: Social classes -- India; Social structure -- India; Social mobility -- India; India -- Social conditions -- 1947-